2015
DOI: 10.1080/00222348.2015.1103430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melanomal Proteins on Sepia Melanin Assembly

Abstract: Keywords Downloaded by [Dalhousie University] at 08:36 11 October 2015 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 Sepia melanin self-assembly; amyloid fibrils; cephalopod ink; scanning electron microscopy; Scanning transmission electron microscopy; Atomic force microscopy. ABSTRACT Melanins are phenol-based pigments with the potential for widespread applications including bioelectronics and tissue engineering. The concentration-dependent structural transition of sepia melanin in water is analyzed. This biopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…To become conductive, the melanin samples need to be coated first. For this purpose, a thin layer of gold [37,38,39] or gold/palladium alloy [40] is often used. Depending on the melanin source, the granule morphology and size range between 30–1000 nm and melanin granules are usually amorphous with irregular shape (Table 3).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To become conductive, the melanin samples need to be coated first. For this purpose, a thin layer of gold [37,38,39] or gold/palladium alloy [40] is often used. Depending on the melanin source, the granule morphology and size range between 30–1000 nm and melanin granules are usually amorphous with irregular shape (Table 3).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…The aqueous solutions of eumelanin (from Sepia officinalis ) were sonicated, centrifugated, lyophilized, and then re-dispersed in ultrapure water. The melanin aqueous suspension was deposited on a disc and the surface was further scanned [35,40,67,68].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Cuttlefish ink (Sepia officinalis) was purified by a method described elsewhere. [23] An ink suspension was obtained by dissolving 100 g of the commercial ink with 200 mL of ultrapure water. The suspension was centrifuged at 12,000 rpm for 15 min at 5 °C (5810R, Eppendorf, Germany) and the supernatants were discarded, while the obtained pellet was resuspended in ultrapure water.…”
Section: Preparation and Functionalization Of Drug-loaded Melanin Nanmentioning
confidence: 99%
“…Srisuk et al reported a concentration-dependent structural transition of sepia melanin in water, in which at high concentration sepia melanin gives the well-known nanospheres whereas dilution of the samples (0.1 mg L −1 and 10 μg L −1 ) gives nanofibers (minimum diameter ca 11 nm, several micrometers in length) exhibiting the structural features of mature amyloid fibrils. 69 In nature, birds use melanosomes to form organized structures for producing colors. Inspired by nature, melanin-like and PDA NPs have been investigated to produce structural colors.…”
Section: The Modulation Of Nanostructures Of Melanin-like Materialsmentioning
confidence: 99%
“…Srisuk et al reported a concentration‐dependent structural transition of sepia melanin in water, in which at high concentration sepia melanin gives the well‐known nanospheres whereas dilution of the samples (0.1 mg L −1 and 10 µg L −1 ) gives nanofibers (minimum diameter ca 11 nm, several micrometers in length) exhibiting the structural features of mature amyloid fibrils …”
Section: The Modulation Of Melanin‐like Materialsmentioning
confidence: 99%